Phytochemicals in Soybeans: Bioactivity and Health Benefits - Li, Yang; Qi, Baokun (Functional Foods and Nutraceuticals, 2022)
Soybeans represent an excellent source of high-quality protein with a low content of saturated fat. They can be made into various foods, such as tofu, soymilk, miso, breakfast cereals, energy bars, and soy cakes. Much research has been carried out on the positive health effects of soybeans, and increasing evidence shows that consumption of soybeans may reduce the risk of osteoporosis, have a beneficial role in chronic renal disease, lower plasma cholesterol, and decrease the risk of coronary heart disease. Phytochemicals in Soybeans: Bioactivity and Health Benefits describes in detail the chemical characteristics of health-promoting components of soybeans and soybean products, their impacts on human health, and emerging technologies about soybean processing and new products. With 22 chapters containing the most recent information associated with soybean products, topics of the chapters include soybeans' role in human nutrition and health, their composition and physicochemical properties, the action mechanism of their physiologic function, processing engineering technology, food safety, and quality control. Key Features: Promotes soybean products as functional foods with advanced processing technology Presents the basic research containing the experimental design, methods used, and a detailed description of the results. Provides a systematic approach to the subject to facilitate a better comprehension of the subject with illustrations and diagrams Includes a comprehensive and up-to-date list of references With contributions from authors around the world who are experts in their field, this book contains new information on the health impacts of soybean consumption, new product development, and alternative technologies of soybean processing, and will be useful for professors and researchers, as well as graduate and undergraduate students alike.